On orders of two transformation semigroups of the boolean - Livinsky, I.V.; Zhukovska, T.G. (Carpathian Mathematical Publications, 2014)
We consider the semigroup O(B_n) of all order-preserving transformations φ : B_n → B_n of ordered by inclusion boolean B_n of n-element set (i.e. such transformations that A B implies φ(A) φ(B)) and its subsemigroup C(B_n) of those transformations for which φ(A) A for all A B_n. Orders of these semigroups are calculated.